Train Station Performance Evaluation Based On Minimum Service Standard (Case Study: Cikarang Station, West Java) - Dermawan, Widodo Budi; Fibriyanto, Nurul (Yayasan Ahmar Cendekia Indonesia, 2020)
As the population grows and the economic level in the Cikarang area increases the movement of the people. Provision of mass transportation or transportation using the train is very necessary to anticipate the congestion that will occur by providing this train station can be an alternative. Therefore, it is necessary to conduct research to assess the performance and quality of service to to find out how much the level of passenger satisfaction with the service performance of the cikarang station. The method used is the Importance Performance Analysis (IPA) and Chi Square Squares. This study uses 100 respondents for each method. Station performance that does not meet Minimum Service Standards such as waiting rooms, boarding rooms and passenger service facilities. From the analysis obtained the average value of the level of passenger satisfaction with the services and facilities of the Cikarang Station, namely the value of the level of performance with an average weight of 3.17 and the value of satisfaction with an average weight of 3.17, from the highest score of 5 and the lowest score 1. Chi Square Test on the Station Cikarang shows that service factors that significantly influence passenger satisfaction are cleanliness and comfort of the toilet.